The Shelf- life of Seasoned Fish Meat Floss (Abon Ikan) Made from Red Tilapia (Oreochromis niloticus Trewavas)Processed by Different Frying Methods - Eko Nurcahya Dewi; Ratna Ibrahim; Nuzulia Yuaniva (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2011)
Seasoned fish meat floss (“abon ikan” ) is a processed fish made from fish meat and traditionally processed by boiling, seasoning and frying. The frying method that is usually used is a deep frying. The unsaturated fatty acids and the oil content in the product cause a rancidity problem during the product is stored at room temperature. The aim of the research is to find out the effect of a deep frying and a pan frying methods application on the seasoned fish meat floss processing using red tilapia and the storage time at room temperature to the rancidity development and the shelf-life of the products based on the rancidity variable analysis (PV, TBA, AASC, Aw values) and the hedonic values of the products. The experimental design used was a completely randomized design with a factorial pattern (2 x 3 ). Based on the chemical analysis results and the hedonic value of the product stored up to 15 days at a room temperature it was found that the product processed by the pan frying method had a better quality and it was not rancid yet. The characteristics of the product were as followed : PV (4.3699 miliequivalent / kg lipid , TBA (3.5215 mg malonaldehyde / kg sample), AASC (0.4727abs unit/g/ml) , Aw(0.47)  whereas the odour and the flavour  value was 7.2 respectively.   Keywords: Seasoned fish meat floss, red tilapia, deep frying, pan frying, quality